Early and Late Results after Surgical Mitral Valve Repair: A High-Volume Center Experience - Götte, Julia; Zittermann, Armin; Deutsch, Marcus-Andre; Schramm, Rene; Bleiziffer, Sabine; Renner, Andre; Gummert, Jan F. (The Thoracic and Cardiovascular Surgeon, 2024)
Background Surgical mitral valve repair is the gold standard treatment of severe primary mitral regurgitation (MR). In the light of rapidly evolving percutaneous technologies, current surgical outcome data are essential to support heart-team-based decision-making.Methods This retrospective, high-volume, single-center study analyzed in 1779 patients with primary MR early morbidity and mortality, postoperative valve function, and long-term survival after mitral valve (MV) repair. Surgeries were performed between 2009 and 2022. Surgical approaches included full sternotomy (FS) and right-sided minithoracotomy (minimally invasive cardiac [MIC] surgery).Results Of the surgeries (mean age: 59.9 [standard deviation:11.4] years; 71.5% males), 85.6% (n = 1,527) were minithoracotomies. Concomitant procedures were performed in 849 patients (47.7%), including tricuspid valve and/or atrial septal defect repair, cryoablation, and atrial appendage closure. The majority of patients did not need erythrocyte concentrates. Mediastinitis and rethoracotomy for bleeding rates were 0.1 and 4.3%, respectively. Reoperation before discharge for failed repair was necessary in 12 patients (0.7%). Freedom from more than moderate MR was > 99%. Thirty-day mortality was 0.2% and did not differ significantly between groups (p = 0.37). Median follow-up was 48.2 months with a completeness of 95.9%. Long-term survival was similar between groups (p = 0.21). In the FS and MIC groups, 1-, 5-, and 10-year survival rates were 98.8 and 98.8%, 92.9 and 94.4%, and 87.4 and 83.1%, respectively.Conclusion MV surgery, both minimally invasive and via sternotomy, is associated with high repair rates, excellent perioperative outcomes, and long-term survival. Data underscore the effectiveness of surgical repair in managing MR, even in the era of advancing interventional techniques.
Keywords: heart; valve; surgery; minimally invasive surgery; reoperation; mitral valve